USE OF COLLABORATIVE LEARNING STRATEGIES IN FORMING INTERPERSONAL INTELLIGENCE WHERE IS NURUL AKBAR PONGKA KAB. BONE - Hajar Humaera Cane; Samsinar Samsinar; Aminullah Aminullah (Education Studies and Teaching Journal (EDUTECH), 2025)
This study examines the application of collaborative learning strategies in developing students' interpersonal intelligence at MA Nurul Akbar Pongka, Bone Regency. Using a qualitative field research design and an educational approach, data were collected through interviews, observations, and documentation. The collaborative strategy was implemented through three stages: planning, implementation, and evaluation. The planning stage involved designing group work that focused on building social character; implementation encouraged positive interactions and joint decision-making; and evaluation included assessing group outcomes, individual participation, and social attitudes. The results showed that collaborative learning improved students' interpersonal intelligence, including self-confidence in communication, listening skills, and conflict resolution. This strategy also fostered cooperation, tolerance, and mutual support among students.